Case Report: Severe Rhabdomyolysis and Multiorgan Failure After ChAdOx1 nCoV-19 Vaccination - Cirillo, Emilia; Esposito, Ciro; Giardino, Giuliana; Azan, Gaetano; Fecarotta, Simona; Pittaluga, Stefania; Ruggiero, Lucia; Barretta, Ferdinando; Frisso, Giulia; Notarangelo, Luigi Daniele; Pignata, Claudio (Frontiers in Immunology, 2022)
Background: Severe skeletal muscle damage has been recently reported in patients with SARS-CoV-2 infection and as a rare vaccination complication. Case summary: On Apr 28, 2021 a 68-year-old man who was previously healthy presented with an extremely severe rhabdomyolysis that occurred nine days following the first dose of SARS-CoV-2 ChAdOx1 nCov-19 vaccination. He had no risk factors, and denied any further assumption of drugs except for fermented red rice, and berberine supplement. The clinical scenario was complicated by a multi organ failure involving bone marrow, liver, lung, and kidney. For the rapid increase of the inflammatory markers, a cytokine storm was suspected and multi-target biologic immunosuppressive therapy was started, consisting of steroids, anakinra, and eculizumab, which was initially successful resulting in close to normal values of creatine phosphokinase after 17 days of treatment. Unfortunately, 48 days after the vaccination an accelerated phase of deterioration, characterized by severe multi-lineage cytopenia, untreatable hypotensive shock, hypoglycemia, and dramatic increase of procalcitonin (PCT), led to patient death. Conclusion: Physicians should be aware that severe and fatal rhabdomyolysis may occur after SARS-CoV2 vaccine administration.